Cost‐Effectiveness of Pharmacist‐Led Deprescribing of NSAIDs in Community‐Dwelling Older Adults. Issue 5 (27th February 2020) - Sanyal, Chiranjeev; Turner, Justin P.; Martin, Philippe; Tannenbaum, Cara
Abstract : OBJECTIVES: Older adults are often prescribed potentially inappropriate medications associated with adverse health outcomes and increased health services utilization. Developing Pharmacist‐led Research to Educate and Sensitize Community Residents to the Inappropriate Prescriptions Burden in the Elderly (D‐PRESCRIBE), a pragmatic randomized clinical trial, demonstrated how a community pharmacist‐led evidence‐based educational intervention successfully empowered community‐dwelling older adults and their physicians to reduce chronic use of inappropriate medications. The objective of this study was to evaluate the cost‐effectiveness of the D‐PRESCRIBE intervention for discontinuing nonsteroidal anti‐inflammatory drugs (NSAIDs). DESIGN: Cost‐effectiveness analysis. SETTING: Canada. PARTICIPANTS: Community‐dwelling adults aged 65 years and older. MEASUREMENTS: Decision analysis combining decision tree and Markov state transition modeling was developed to estimate the cost‐effectiveness of D‐PRESCRIBE (NSAIDs) compared with usual care from a Canadian healthcare system perspective with a time horizon of 1 year. Data from the D‐PRESCRIBE trial and published literature were used to calculate effectiveness, utilities, and costs. Reference case and scenario analyses were conducted using probabilistic modeling. Sensitivity analyses assessed the robustness of the reference case model. RESULTS: D‐PRESCRIBE (NSAIDs) was less costly (−$1008.61) and more effective (.11 quality‐adjusted life‐years [QALYs]) than usual care and was the dominant strategy. At willingness‐to‐pay thresholds of $50 000 per QALY and $100 000 per QALY, D‐PRESCRIBE (NSAIDs) incurred a positive incremental net benefit compared with usual care, suggesting it is cost‐effective. Compared with the reference case, scenario analyses gave comparable QALYs with modest variation in cost estimates. CONCLUSION: For community‐dwelling older adults, D‐PRESCRIBE (NSAIDs) provides greater benefits at lower system costs, making it a compelling strategy to reduce the use and harms associated with chronic NSAID consumption. Our findings support reimbursing community pharmacists' clinical professional services for deprescribing inappropriate NSAIDs in community‐dwelling older adults. J Am Geriatr Soc 68:1090–1097, 2020